Coupling relationship of industrial structure and coastal utilization in stage-specific development of urban bay: a case study of Xiamen, China (1958–2020) - Weida Lin; Fangfang Shu; Fusheng Luo; Yunpeng Lin; Yuting Lin; Zhijie Chen; Yunhai Li (Frontiers in Marine Science, 2026)
Introduction Coastal zones in bay cities are characterized by high population density, concentrated economic activities, and integrated socio-ecological systems. The dynamic interaction between industrial structural evolution and coastal development in such areas exerts profound impacts on both regional economic growth and ecological sustainability, making it critical to clarify their correlation. Methods By integrating historical marine maps (1958–2020) and remote sensing images (1986–2020) of Xiamen Bay, we extracted the coastline length and utilization data of Xiamen (a typical bay city). Artificial coastlines were categorized into four types based on their functional attributes. The Spearman rank correlation coefficient was then applied to analyze the relationships between coastline length, utilization type, and urbanization indicators, linking these variables to the structure of the primary, secondary, and tertiary industries. Results and Discussion The results indicate that: 1) From 1958 to 2020, the natural coastline length of Xiamen Bay decreased by 283.57 km, accompanied by continuous expansion of artificial coastlines. Specifically, First-type artificial coastline increased by 152.73 km (1958–2002) but decreased by 134.48 km (2002–2020); Second and third type coastlines expanded by 117.07 km and 154.61 km respectively; Fourth-type coastline emerged after 2002 and reached 23.23 km in 2020. 2) At the regional scale, First-type coastline expansion showed a phased positive correlation with the primary industry; Second and third type coastline development was positively correlated with the secondary and tertiary industries (but negatively correlated with the primary industry). 3) The evolution of Xiamen’s coastal zone has shifted from a single economic benefit orientation to a synergistic “economic–ecological–social” model, corresponding to four stages: agricultural reclamation-dominated, initial export-oriented economy, bay-type city construction, and high-quality development transition. Notably, this shift is closely tied to industrial structure adjustments, providing a reference for bay cities to balance economic growth and coastal ecological protection.